Membrane-based electrolysis for hydrogen production: a review - Ahmad Kamaroddin, Mohd Fadhzir; Sabli, Nordin; Tuan Abdullah, Tuan Amran; Siajam, Shamsul Izhar; Chuah, Luqman Abdullah; Abdul Jalil, Aishah; Ahmad, Arshad (MDPI, 2021)
Hydrogen is a zero-carbon footprint energy source with high energy density that could be the basis of future energy systems. Membrane-based water electrolysis is one means by which to produce high-purity and sustainable hydrogen. It is important that the scientific community focus on developing electrolytic hydrogen systems which match available energy sources. In this review, various types of water splitting technologies, and membrane selection for electrolyzers, are discussed. We highlight the basic principles, recent studies, and achievements in membrane-based electrolysis for hydrogen production. Previously, the Nafion™ membrane was the gold standard for PEM electrolyzers, but today, cheaper and more effective membranes are favored. In this paper, CuCl–HCl electrolysis and its operating parameters are summarized. Additionally, a summary is presented of hydrogen production by water splitting, including a discussion of the advantages, disadvantages, and efficiencies of the relevant technologies. Nonetheless, the development of cost-effective and efficient hydrogen production technologies requires a significant amount of study, especially in terms of optimizing the operation parameters affecting the hydrogen output. Therefore, herein we address the challenges, prospects, and future trends in this field of research, and make critical suggestions regarding the implementation of comprehensive membrane-based electrolytic systems.